Credit Risk Management and Measurement Econometric and Empirical Model in the Banking System: Array - Lulaj, Enkeleda; Mazreku, Ibish; Dragusha, Blerta (Acta Universitatis Danubius. Œconomica, 2020)
The scientific paper begins with research on the financial-credit stability of the banking system in Kosovo, in the Western Balkan countries, in the Eurozone and beyond, to analyze the importance and effect of indicators on the stability of the banking system. This research paper focuses on management, analysis and measurement of credit risks. Firstly, the performance of the banking system is analyzed in different periods (specifically during the last 10 years), making comparability with other countries. Then, the financial- credit risk indicators are analyzed through: empirical time series analysis, credit shock analysis, credit index analysis, descriptive analysis, factorial analysis, reliability analysis. Finally, in order to protect the banking system from the failure or decline of financial stability at all times and continually the quality of loans and other assets should be assessed. This paper will assist future researchers for further analysis in different countries.